Planning, Strategic Planning, Planning of Marketing - Ivanov, Pencho (Research Papers, 2006)
Marketing planning of organizations may be studied from many angles. From technological point of view, marketing planning premises setting of objectives, developing marketing strategies, drafting agendas resource back-up (including financial support) of marketing activities. Marketing planning however is not only, even not that much, of technology. Marketing planning is a philosophy of company management, including marketing management. That management philosophy is grounded on the idea that marketing should be carries out on the basis of preliminary defined objectives to which the organization’s resources are adjusted by qualitative and quantitative changes, not the other way around. The effective marketing management eliminates the possibility the available resources to determine marketing objectives. To this effect the conclusion is that marketing planning is aggregation of technological procedures upon the logic of strategic planning irrespectively the horizon of planning (long-term or short-term). The above also leads to the conclusion that marketing planning is the modern form of strategic management and planning.